Identifikasi Jamur Pada Pasien Penderita Tuberkulosis Paru di RSUP H. Adam Malik Medan - Dewi Setiyawati; Suryani M.Florence Situmeaang (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2021)
Pulmonary tuberculosis’s an inflammation of the lung parenchrose caused caused by bacterium Mycobacterium tuberculosis. Pulmonary mycosis’s a disease that’s often undiagnosed because the typical clinical symptom for this disease’re unknown. A person with pulmonary mycosis will show non-specific symptom of chronic cough which is often regarded as a symptom of pulmonary tuberculosis. The study aims to identify Aspergillus sp in patients with pulmonary tuberculosis in H. Adam Malik Central Public Hospital Medan. Tye type of research used’s descriptive research that will describe about Aspergillus sp in patients with pulmonary tuberculosis in H. Adam Malik Central Public Hospital Medan. The population was all patients of Tuberculosis Lung at H. Adam Malik Central Public Hospital. The results of this study from 5 sampel show that sampel number 1 found a Aspergillus fumigatus and Aspergillus niger, sampel number 4 found a Aspergillus flavus, sampels number 2,3 and 5 found a Candida albicans. Based on the results of the study can be conclude that the factors that cause the growth of fungus is from the provision of Anti-Tuberculosis Drugs in a long time that only suppress the bacteria from Pulmonary Tuberculosis